Given:
![\begin{gathered} y=-2x+4\ldots\ldots\ldots\ldots\ldots(1) \\ y=x^2+4x+13\ldots\ldots\ldots\ldots\ldots(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/xqdlryrfjkvrflr213jxc3jct65d4a6hjz.png)
To find: The y-coordinate of the solution
Step-by-step explanation:
Substituting equation (1) in equation (2) and solving, we get
![\begin{gathered} -2x+4=x^2+4x+13 \\ x^2+4x+13+2x-4=0 \\ x^2+6x+9=0 \\ (x+3)(x+3)=0 \\ x=-3,-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7eda1qfo8wtbrzc4vx95qij6apjj60i0gu.png)
Substitute the x-value in equation (1) we get,
![\begin{gathered} y=-2(-3)+4 \\ y=6+4 \\ y=10 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/4hn448j5z2mqbbi448snotinpmol6qoavt.png)
Thus, the solution is ( -3, 10).
Final answer:
The y-coordinate of the solution is 10.